PENGGUNAAN PENDEKATAN CTL DENGAN MODEL PASA (PICTURES AND STUDENT ACTIVE) PADA MATA PELAIARAN GEOGRAFI UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA KELAS XI IPS-1 MAN NGORO JOMBANG - Malisun, Malisun (J-PIPS (Jurnal Pendidikan Ilmu Pengetahuan Sosial), 2015)
This study used a qualitative approach with classroom action research (PTK). The main goal of this research is to understand at the various possibilities efforts to improve the achievement of learners Class XI IPS-1 Â Madrasah Aliyah Genukwatu on subjectsâ€™ geography through approach Contextual Teaching and Learning (CTL) with a model of P a SA (Pictures and Student Active). This research took place in the first semester of the school year 2013/2014, performed with 2 cycles. The learning process with CTL approach through PASA models implemented by stages (1) the distribution of a small group (2) students describe the pictures (3) review and analyze each image (4) discuss the pictures (5) perform oral presentations (6) carry out post-test in the form of quizzes and problems of objective/ subjective. The results showed that the learning outcomes with PASA models can improve the processes and outcomes of learning. In cycle I Class XI IPS-1yang totaling 25 students who completed study were 20 students (80%), while incomplete 5 students (20%) in the second cycle of a significant increase which students completed 100%.Keywords: improve the achievement, CTL, Picture and Student Active